The use of nanoparticulates to treat breast cancer. (October 2017) - Tang, Xiaomeng; Loc, Welley S; Dong, Cheng; Matters, Gail L; Butler, Peter J; Kester, Mark; Meyers, Craig; Jiang, Yixing; Adair, James H
Breast cancer is a major ongoing public health issue among women in both developing and developed countries. Significant progress has been made to improve the breast cancer treatment in the past decades. However, the current clinical approaches are invasive, of low specificity and can generate severe side effects. As a rapidly developing field, nanotechnology brings promising opportunities to human cancer diagnosis and treatment. The use of nanoparticulate-based platforms overcomes biological barriers and allows prolonged blood circulation time, simultaneous tumor targeting and enhanced accumulation of drugs in tumors. Currently available and clinically applicable innovative nanoparticulate-based systems for breast cancer nanotherapies are discussed in this review.